Determinants for adoption of e-banking among bank's customers - Normaizatul Akma Saidi; Nor Amyrashahira Azib; Nor Azlin Amran; Nor Ezzati Syairah Sulham; Nor Fathiah Fairul Anuar; Noraida Saidi (Global Academic Excellence, 2016)
The use of internet has been advanced commercially in most business activities including in financial services industry. This internet technology has changed the way of banks deliver their services towards the customer and the behaviours of customer towards adopting their banking needs. E-banking has increasingly become a preferred distribution channel and one of the most popular banking services adopted by customers. The general objective of this study is to discuss the determinants for adoption of e-banking among customers. Therefore, this study provide the conceptual framework of perceived ease of use, perceived usefulness, demographic characteristics and internet experience which affect the adoption of e-banking. These four determinants are found to be significant in affecting the adoption of e-banking among bank’s customers.